2012
DOI: 10.2500/aap.2012.33.3575
|View full text |Cite
|
Sign up to set email alerts
|

A study of IgE sensitization and skin response to histamine in Asian-Pacific American adults

Abstract: Allergic disorders and skin response to histamine have been noted to vary in different ethnicities. We investigated IgE-mediated allergic sensitization and skin response to histamine in Asian Pacific Americans (APAs), black and Hispanic Americans, and white adults. A retrospective questionnaire-based study was performed of 2222 adults presenting at a New York City allergy referral center from 1994 to 2003. Questionnaire data included sex, age, and ethnicity and personal and family history of atopic disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, the seasonal variation of histamine reactivity was also analyzed in the present study. 5,7 Nevertheless, the present study has several limitations. First, the sample size was too small to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the seasonal variation of histamine reactivity was also analyzed in the present study. 5,7 Nevertheless, the present study has several limitations. First, the sample size was too small to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 78%
“…Histamine skin reactivity can differ depending on race and age [24]. Other studies have shown that skin test results had seasonal variations [10,12]. However, the present study has a relatively homogeneous population sample consisting of Korean children.…”
Section: Discussionmentioning
confidence: 85%
“…To even further increase the accuracy of SPT results, the HEP-index can be calculated, to rule out differences in skin reactivity. There are several factors that contribute to this difference, e.g., poly-sensitised patients and patients with mould sensitisation have significantly higher skin reactions [ 14 ] and the skin response varies in different ethnicities [ 15 ]. Furthermore, differences in technique of performing SPTs (inter-observer variability) contribute to the variation in wheal size [ 4 ].…”
Section: Discussionmentioning
confidence: 99%